,,Making the World Safe for Democracy“: Einige Beobachtungen zum Verhältnis von Internationaler Rechtsordnung, Demokratie und globaler Sicherheit - Mattias Kumm (Normative Konstituenzien der Demokratie, 2024)
– The article analyzes how in WWII the Roosevelt administration conceived of and structured the new world order they were building to ,,make the world safe for democracy“. It then goes on to analyze how in its current form that order fails in this task. The current international legal order fosters and enables great power competition by structurally failing to provide mechanisms for holding accountable great powers when they illegally use force. Such structural lack of accountability lies at the heart of dynamics of resentment driven establishment of counter-power by other states. This in turn leads to militarized great power competition with great risks of major wars. Reforms aimed at holding great powers legally accountable are not only compatible with democracy, they are the precondition for successfully institutionalizing a system of international law that may actually succeed in making the world safe for democracy.
Keywords: 320